2022
DOI: 10.1007/s11356-022-24201-3
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and properties of phosphinic acid–functionalized polyacrylonitrile hollow fiber membrane for heavy metal adsorption

Abstract: In this study, phosphorylated polyacrylonitrile hollow ber membrane was synthesized by reacting aminated polyacrylonitrile hollow ber membrane with phosphinic acid in a Mannich reaction. The batch single factor measurements revealed that the PPAN membrane had an outstanding ability for Hg 2+ adsorption. Thermodynamic investigations indicated that the adsorption process was homogenous, and the theoretical maximum adsorption capacity predicted by the Langmuir model was 371.75 mg•g − 1 . The PPAN membrane was abl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 49 publications
(27 reference statements)
1
1
0
Order By: Relevance
“…These results showed that, as somewhat expected from Equation (15), the iron flux increased with the increase in the initial metal concentration in the feed phase [38].…”
Section: Influence Of the Initial Iron(iii) Concentration In The Feed...supporting
confidence: 78%
See 1 more Smart Citation
“…These results showed that, as somewhat expected from Equation (15), the iron flux increased with the increase in the initial metal concentration in the feed phase [38].…”
Section: Influence Of the Initial Iron(iii) Concentration In The Feed...supporting
confidence: 78%
“…In the case of membrane technologies, supported liquid membranes both in flat-sheet or hollow fiber modules are gaining special consideration in the recovery of metals [ 15 , 16 , 17 , 18 ]. In the case of hollow fiber membrane processing, one of the more advanced developments is the so-called pseudo-emulsion-based hollow fiber strip dispersion (PEHFSD), which is characterised by its ability to afford high mass transfer rates of solutes and is accompanied by high selectivity by the use of specific carriers or extractants.…”
Section: Introductionmentioning
confidence: 99%